2019
DOI: 10.1111/eip.12886
|View full text |Cite
|
Sign up to set email alerts
|

Google search activity in early psychosis: A qualitative analysis of internet search query content in first episode psychosis

Abstract: Aim Manually explore the Google search queries of individuals with first episode psychosis prior to their first hospitalization, in effort to identify common themes and search interests during the period of emerging illness. Methods Individuals hospitalized for psychosis between December 2016 and September 2017 provided access to their Google archive data for manual qualitative evaluation of search content. Searches conducted during the 6‐month time period prior to the participant's first hospitalization for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Recently, studies have focused on the prevalence of substance use among youth and young adults with FEP and have demonstrated the subsequent impact of use on physical health, psychiatric symptoms, and treatment engagement (Abdel-Baki et al, 2017; Oluwoye, Monroe-DeVita, et al, 2019; Schoeler et al, 2016; Weibell et al, 2017). Several qualitative studies among youth and young adults with early psychosis have also examined factors (e.g., perceived norm, coping mechanism) that contribute to substance use and the impact of substance use on relationships and social networks among youth and young adults with early psychosis (Griffiths et al, 2019; Kirschenbaum et al, 2020; Lobbana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have focused on the prevalence of substance use among youth and young adults with FEP and have demonstrated the subsequent impact of use on physical health, psychiatric symptoms, and treatment engagement (Abdel-Baki et al, 2017; Oluwoye, Monroe-DeVita, et al, 2019; Schoeler et al, 2016; Weibell et al, 2017). Several qualitative studies among youth and young adults with early psychosis have also examined factors (e.g., perceived norm, coping mechanism) that contribute to substance use and the impact of substance use on relationships and social networks among youth and young adults with early psychosis (Griffiths et al, 2019; Kirschenbaum et al, 2020; Lobbana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar computational methods have identified associations between social media activity and behavioral health [22][23][24][25][26][27][28][29]. Few studies to date, however, have explored the link between search activity and psychiatric illness, beyond retrospective selfreport [30]. Furthermore, while promising, internet activity research to date has been limited by the fact that it has been conducted nearly exclusively using search data from anonymous individuals who self-report a diagnosis online, and has yet to be carried out in real world clinical settings, using participant-contributed search data, with clinically validated symptoms and diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…These included STBs, help seeking, symptoms of mental health disorders, trauma and negative life events, and drugs of abuse. A similar method of categorization was previously used successfully by our group in a study of the search queries of patients with psychosis [ 8 ]. These thematic categories coincided with factors that are recognized as modulators of suicide risk [ 19 ] and were chosen because they were thought to be sufficiently broad enough to capture a wide array of behavioral health–related symptoms and behaviors that are searched for by individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, traditional clinical assessment does not occur often enough to reveal the day-to-day fluctuations of STBs that patients experience [5][6][7]. Prior studies have demonstrated that data gathered from various digital platforms, including smartphone apps, wearable devices, social media, and internet search engines, can enhance the traditional evaluation of STBs and other psychiatric symptoms [5,6,[8][9][10]. The use of these information sources is acceptable to patients [9,11,12], and data gathered from digital platforms can be collected passively in real time and in the same settings in which patients are likely to experience symptoms.…”
Section: Introductionmentioning
confidence: 99%